Market concentration and product variety under spatial competition : evidence from retail gasoline - Georg Goetz; Klaus Gugler (Center for Economic Studies and ifo Institute (CESifo), 2004)
We show that for a spatially differentiated economy reduced product variety is the likely outcome of mergers except in cases where exit costs in relation to (outlet-specific) fixed costs are high. Our empirical analysis of the Austrian retail gasoline market confirms that increases in concentration reduce product variety. Ignoring this product variety effect is likely to lead to an underestimate of market power in structural merger analysis.
Keywords: L11; L90; L13; 330; spatial product differentiation; retail gasoline; mergers; concentration; Produktdifferenzierung; Räumlicher Wettbewerb; Fusion; Wirtschaftskonzentration; Tankstelle; Theorie; Österreich